1993
DOI: 10.1159/000292682
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Surface Epithelium and Human Ovarian Cancer

Abstract: Approximately 80–90% of adult ovarian cancers are assumed to originate from ovarian surface cells. The morphology of the ovarian surface epithelium changes constantly, exhibiting features such as crypts, inclusion cysts, villous processes and different forms of mÜllerian epithelium. The unique nature of ovarian surface features and their absence in the immediately adjacent peritoneal mesothelium suggest that local factors may play an important part in modifying the growth and morphology of the ovarian surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The carcinogenic effects of estrogens on the surface epithelium of the ovary has been extensively documented [25,26], but the mechanisms by which these steroids promote tumorigenesis remain unresolved. Our studies demonstrate the existence of a direct relationship between E2 and E-cad m R N A levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The carcinogenic effects of estrogens on the surface epithelium of the ovary has been extensively documented [25,26], but the mechanisms by which these steroids promote tumorigenesis remain unresolved. Our studies demonstrate the existence of a direct relationship between E2 and E-cad m R N A levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although hormonal contraceptives have been shown to be effective in reducing the risk of developing ovarian carcinoma, the mechanisms by which these agents act have not been elucidated [26]. High levels of estrogens and progestins are known to be capable of down-regulating the estrogen receptor [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A number of more recent molecular, genetic, and immunohistochemical studies have provided evidence that many or most pelvic and extrauterine high-grade serous carcinomas likely originate in the fallopian tubes. 111 The current study, an examination of a series of low-stage ovarian carcinomas including low-stage HGSCs, supports the idea that many HGSCs do not arise within the ovary; as compared to the other major ovarian carcinoma subtypes, low-stage HGSCs are significantly more often distributed bilaterally and multifocally with ovarian surface involvement of relatively small ovaries, patterns which, with the exception of SC, are almost always equated with metastasis to the ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…The exactly initiating cell population for epithelial ovarian carcinoma (EOC) remains to be defined. Different evidences have suggested that EOC originate from the ovarian surface epithelium, inclusion cysts lined [4-7] or alternatively, the fallopian tube epithelium [8] or components of the secondary Müllerian system, including the epithelial cells of the rete ovarii, paraovarian/ paratubal cysts, endosalpingiosis, endometriosis or endomucinosis [9-13]. …”
Section: Backgroundsmentioning
confidence: 99%